Applying an integrated theoretical lens to evaluate the perceived effectiveness of a computer-based reading development course in higher education - Lenong, B.; Holtzhausen, S. M. (South African Journal of Higher Education, 2023)
South African higher education institutions have implemented different means of developing first-year students’ English language abilities. In 2007, a university of technology introduced a compulsory computer-based reading development course to help first-year students improve their reading ability. A decade after implementation, an investigation into the effectiveness of the course, from the students’ perspectives, became imperative. This article reports on an evaluation of the perceived effectiveness of the course that was undertaken in 2018. A questionnaire survey of 269 Bachelor of Education students, followed by focus group interviews, were used to gather data. The design of the study was informed by a theoretical lens that highlights a set of directives that are underpinned by theory on student engagement and creating motivational conditions. This theory is integrated with theory emanating from studies on technology acceptance and use of the computer as medium. The findings indicate that the course was generally perceived as easy to use, useful and engaging, and that a good level of inclusion had been established. A few aspects needed attention, however, and pointed to the institution’s obligation to ensure that all conditions are adhered to for the creation of a motivational environment for culturally diverse communities. The article not only touches upon the practical implementation of reading development in higher education, but also describes in detail an integrated theoretical lens that can be customised to evaluate the perceived effectiveness of many technologically enhanced teaching and learning applications in higher education.